INT J ENV SCI ED 2016
DOI: 10.12973/ijese.2015.280a
|View full text |Cite
|
Sign up to set email alerts
|

Investigating High School Students’ Understanding of Chemical Equilibrium Concepts

Abstract: This study investigated the year 12 students' (N = 56) understanding of chemical equilibrium concepts after instruction using two conceptual tests, the Chemical Equilibrium Conceptual Test 1(CECT-1) consisting of nine two-tier multiple-choice items and the Chemical Equilibrium Conceptual Test 2(CECT-2) consisting of four structured questions. Both these tests were administered before and after the intervention. Students' responses to the items in both the instruments indicated limited understanding of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
4
24
0
1
Order By: Relevance
“…This misconception, which is consistently was experienced by 23.3% of students and indicated that students do not understand that catalyst decreases the activation energy of both forward and reverse reactions, not just the forward reaction. This misconception is similar to that reported for first-degree students of science education study program in Turkey (Ozmen, 2008), in Middle School students in Malaysia (Karpudewan et al, 2015), and Izmir Turkish Middle School (Sendur et al, 2011).…”
Section: Misconceptions About Catalyst and Rate Of Reactionsupporting
confidence: 82%
See 1 more Smart Citation
“…This misconception, which is consistently was experienced by 23.3% of students and indicated that students do not understand that catalyst decreases the activation energy of both forward and reverse reactions, not just the forward reaction. This misconception is similar to that reported for first-degree students of science education study program in Turkey (Ozmen, 2008), in Middle School students in Malaysia (Karpudewan et al, 2015), and Izmir Turkish Middle School (Sendur et al, 2011).…”
Section: Misconceptions About Catalyst and Rate Of Reactionsupporting
confidence: 82%
“…Some of them are as follows; The forward reaction rate becomes faster at equilibrium (Hackling & Garnett, 1985); The state of equilibrium occurs when the concentrations of the reactants and products remain the same (Barke et al, 2009;Hackling & Garnett, 1985;Nakhleh, 1992;Yakmaci-Guzel, 2013); The increase in temperature causes the forward reaction rate to decrease and the reverse reaction rate to increase (Barke et al, 2009;Bilgin & Uzuntiryaki, 2003;Hackling & Garnett, 1985); On the equilibrium, reactions will no longer occur (Nakhleh, 1992). Equilibrium is a static process (Barke et al, 2009;Yakmaci-Guzel, 2013); In exothermic reactions, an increase in temperature will decrease the rate of the forward reaction (Banerjee, 1991;Sozbilir et al, 2010); Increasing temperature increases the rate of the reverse reaction since the equilibrium is shifted to the left (Banerjee, 1991;Yan & Subramaniam, 2016); In the CE condition the large vale of K causes the forward reaction to take place faster (Banerjee, 1991;Bilgin & Uzuntiryaki, 2003;Hackling & Garnett, 1985); The addition of reactants (solid phase) in a heterogeneous system causes a shift from the added side (Karpudewan et al, 2015;Piquette & Heikkinen, 2005;Sendur et al, 2011); The addition of a reactant at the gas equilibrium system will shift the equilibrium towards products (Karpudewan et al, 2015); Catalysts cause an increase in product concentration (Bilgin & Uzuntiryaki, 2003;Gorodetsky & Gussarsky, 1986;Hackling & Garnett, 1985;Voska & Heikkinen, 2000); Based on the results above, it shows that misconceptions occur in almost all concepts of CE.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is a reaction in sub microscopic so it called dynamic equilibrium. Because of this characteristic, chemical equilibrium considered one of the most difficult in the general senior secondary school chemistry (Karpudewan et al, 2015) and experienced misconception (Jusniar et al, 2020). Various studies have been carried out to visualize the process of chemical equilibrium.…”
Section: Literature Review Chemical Equilibriummentioning
confidence: 99%
“…To understand the learning process and outcome for this topic, and to select suitable teaching methods, researchers have conducted various research studies on students' understanding of chemical equilibrium. Students' misconceptions (Akkus, et al, 2011;Barke, et al, 2009;Hackling & Garnett, 1985;Karpudewan, et al, 2015;Özmen, 2008;Quílez, 2004;Quílez-Pardo & Solaz-Portolés, 1995), mental models (Chiu, et al, 2002), and conceptual structures (Gorodetsky & ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ Hoz, 1985;Gussarsky & Gorodetsky, 1988Wilson, 1994Wilson, , 1996 for chemical equilibrium have been identified and analyzed. A deeper understanding of students' thinking regarding chemical equilibrium can be utilized to develop more effective teaching methods to improve the classroom teaching (Akkuş, et al, 2003;Maia & Justi, 2009;Ollino, et al, 2018;van Driel, et al, 1998).…”
Section: Introductionmentioning
confidence: 99%